2019
DOI: 10.15376/biores.14.1.1317-1332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resin cleaning process on adhesion strength of water-based varnishes

Abstract: The purpose of this study was to determine how resin, a side compound of wood, and resin cleaning methods affect the adhesion strength of water-based varnishes. For this purpose, scots pine (Pinus sylvestris L.), black pine (Pinus nigra subsp.), larch (Larix decidua Mill.), and spruce (Picea abies (L.) H. Karst.), woods with different amounts of resin in their anatomical structure were examined. Physical and chemical resin cleaning procedures were applied to the samples using acetone, cellulosic (lacquer) thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The increase in the layer thickness of polymer-based varnishes has been stated to have an impact on increasing the surface adhesion resistance (Budakci, 1997), and that the roughness, gloss and surface adhesion resistance of various kinds of water-based varnishes, which are applied with varied methods on different types of wood, have lower values than solvent-based varnishes (Yakın, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the layer thickness of polymer-based varnishes has been stated to have an impact on increasing the surface adhesion resistance (Budakci, 1997), and that the roughness, gloss and surface adhesion resistance of various kinds of water-based varnishes, which are applied with varied methods on different types of wood, have lower values than solvent-based varnishes (Yakın, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been determined that the increase in the lm layer of the varnishes (in polymer-based varnishes) is parallel with the increase in the surface adhesion resistance (Budakci, 1997). In the literature, it has been stated that adhesion in polyurethane varnish gives better results than other varnishes (Sonmez, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…When Scots pine and chestnut tree species were used in outdoor conditions after impregnation and varnishing, higher hardness values were obtained with polyurethane varnish than with synthetic varnish in both tree species (Peker, 1997). When examining the effect of layer thickness on wood varnishes, it was seen that the third layer varnish applications caused an increase in glossiness (Budakci, 1997). It was observed that the glossiness of waterbased varnishes was lower than that of solvent-based varnishes (Yakin, 2001).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…As a result of the research, it was stated that chestnut wood showed less color change when left outdoors than Scots pine wood and that polyurethane varnish affected the hardness of chestnut and Scots pine wood to the first degree and synthetic varnish to the second degree [18]. Budakçı (1997), after applying different varnish types to wood materials, examined the surface adhesion resistance, hardness, and gloss value of the varnish layer thickness and found that acrylic as the varnish type and oak as the wood type had the highest value in the layer thickness resulting from 3layer application in surface adhesion resistance. It was concluded that synthetic varnish had the most negligible value as varnish type, and pine and beech trees had the most negligible value as layer thickness in the 1-coat application and wood type [19].…”
mentioning
confidence: 99%
“…Budakçı (1997), after applying different varnish types to wood materials, examined the surface adhesion resistance, hardness, and gloss value of the varnish layer thickness and found that acrylic as the varnish type and oak as the wood type had the highest value in the layer thickness resulting from 3layer application in surface adhesion resistance. It was concluded that synthetic varnish had the most negligible value as varnish type, and pine and beech trees had the most negligible value as layer thickness in the 1-coat application and wood type [19].…”
mentioning
confidence: 99%